5-Aminolevulinic acid loaded ethosomal vesicles with high entrapment efficiency for in vitro topical transdermal delivery and photodynamic therapy of hypertrophic scars. Issue 46 (10th November 2016) - Zhang, Zheng; Chen, Yunsheng; Xu, Heng; Wo, Yan; Zhang, Zhen; Liu, Ying; Su, Weijie; Cui, Daxiang; Zhang, Yixin
Abstract : 5-Aminolevulinic acid loaded ethosomal vesicles with high entrapment efficiency have excellent penetration and photodynamic therapy for hypertrophic scars in vitro . Abstract : Photodynamic therapy (PDT) with 5-aminolevulinic acid (ALA) is an alternative therapy for hypertrophic scars (HS), which destroys human hypertrophic scar fibroblasts (HSF). However, the poor permeability of ALA both in HS tissue and HSF significantly restricts the PDT of HS. To overcome these barriers, ALA-loaded ethosomal vesicles (ALA-ES) were developed by a pH gradient active loading method and characterized by morphology, entrapment efficiency (EE) and stability. Results show that prepared ALA-ES are homogenous spherical lamellar vesicles, 53 ± 7 nm in size, 50.6 ± 2.3% in EE and have excellent stability. In vitro transdermal delivery studies through HS tissue were carried out by using Franz diffusion cells. Compared to the traditional ALA hydroalcoholic solution (ALA-HA), ALA-ES achieve higher drug retention in less administration time, and fluorescence microscopy showed that ALA-ES penetrate into the deeper dermis of HS in a shorter time, indicating that ALA-ES can enhance the penetration of ALA into HS. Additionally, ALA-ES was visualized in HS tissue for the first time by transmission electron microscopy (TEM). The irregular and collapsed ALA-ES suggest that they can squeeze through narrow spaces to the target area and release ALA into HS. Taking HSF as the target, the transcellular delivery of ALA-ES into HSF cells was investigated by intracellular protoporphyrin IX (PpIX) accumulation. The efficiency of PDT for HSF cells, including the formation of reactive oxygen species (ROS) and cell apoptosis, were also well investigated. Furthermore, the detailed changes of HSF were observed by TEM. The results strongly indicate that ALA-ES can facilitate ALA penetration into HSF cells, and can cause a higher level of cell apoptosis or necrosis than ALA-HA. ALA-ES with high EE is therefore a promising transdermal delivery system for topical ALA administration and has great potential in ALA-PDT of HS.